Magnetic arms of NGC 6946 traced in Faraday cubes at low radio frequencies. Issue 6 (11th September 2018) - Chupin, A.; Beck, R.; Frick, P.; Heald, G.; Sokoloff, D.; Stepanov, R.
Abstract : Magnetic fields in galaxies exist on various spatial scales. Large‐scale magnetic fields are thought to be generated by the α  − Ω dynamo. Small‐scale galactic magnetic fields (1 kpc and below) can be generated by tangling the large‐scale field. The analysis of field structures with the help of polarized radio continuum emission is hampered by the effect of Faraday dispersion (due to fluctuations in magnetic field and/or thermal electron density), which shifts the signals from large to small scales. At long observation wavelengths, large‐scale magnetic fields may become invisible, as in the case of the spectro‐polarimetric data cube of the spiral galaxy NGC 6946 observed with the Westerbork Synthesis Radio Telescope in the wavelength range 17–23 cm. The application of rotation measure (RM) synthesis alone does not overcome this problem. We propose to decompose the Faraday data cube into data cubes at different spatial scales by a wavelet transform. Signatures of the "magnetic arms" observed in NGC 6946 at shorter wavelengths then become visible. Our method allows the use of small‐scale structures as tracers of large‐scale magnetic field patterns in data cubes at long wavelengths, as provided by new‐generation radio telescopes.